The Potential Of Wollastonite As A New Filler For Natural Rubber Compounds - Hoang, Thi Bich Diep (2013)
Wollastonite or calcium silicate, (CaSiO3) has potential as a new type of filler in natural rubber (NR) compounds. The curing characteristics, mechanical properties, swelling behavior, thermal stability and morphology of wollastonite filled NR compounds were investigated. Four series of experiments were performed. All NR compounds were prepared using a two roll mill with different filler loading from 0 to 40 phr. In the first series, the effects of different wollastonite loading on the properties of NR compounds were studied. Results indicated that the cure time (t90), scorch time (ts2), tensile strength and elongation at break (Eb) decreased, whereas, maximum torque (MH), tensile modulus, hardness, thermal stability and swelling behavior increased with wollastonite loading. The second series, the effect of physical ball mill treated wollastonite on the properties of NR compounds was investigated. Treated wollastonite improved the properties of NR compounds as compared to untreated wollastonite. The third series, the effect of 1 phr of 3- aminopropyltriethoxysilane (APTES) as silane coupling agent was studied. The presence of APTES showed an improvement in the properties of NR compounds. This was due to the presence of APTES, which enhanced the rubber-filler interaction of NR compounds. In the last series, the influence of partial replacement of wollastonite by carbon black or calcium carbonate was investigated. The substitution of wollastonite by commercial fillers have improved the properties of NR compounds.